Institutional Orientation Model of Vocational Technical Guidance: An Analysis of the Instituto Nacional de Aprendizaje (Costa Rica) - Fallas-Vargas, Manuel Arturo; Gamboa-Jiménez, Alejandra (Revista Electrónica Educare, 2023)
Objective. To analyze the institutional orientation model enveloping the reality of the discipline at the Instituto Nacional de Aprendizaje [the National Training Institute known as INA]. The analysis is based on work performance, the functions dictated by the Civil Service, and the legislation supporting the orientation work according to the development of professional practice. Method. This article adheres to a naturalistic paradigm and employs a phenomenological design. The study used a focus group method comprising four participants for data collection purposes. Results. Orientation is projected as a professional action influenced by a range of factors belonging to the vocational field and with a work-oriented emphasis. INA’s institutional orientation model can only be understood within its legal framework and technical guidelines supporting professional performance across various regions, centers, and specialties. Discussion. Professional practice’ demands are perceived as a challenge. On the one hand, the challenge is due to the fulfillment of technical guidelines established at the institutional level to comply with quality standards. On the other hand, it is posed due to the necessity of attending to a large population, besides the discipline challenge to embrace in the face of a new restructuring within the INA.